MODERNIZATION OF EDUCATIONAL PRACTICES IN PEDAGOGICAL UNIVERSITIES - Trotsko, Hanna (The Modern Higher Education Review, 2018)
In the article are considered transformations of educational practices holding in pedagogical universities taking into account modern mobile sociocultural process. It is proved that moral senses of university idea realize society transformation potential of education thanking to involving to the system of studying and educational practices. Societal self-representation of pedagogical education is possible only because of humanized strategy of society modernization which expects wide involving of pedagogical ideas, norms, values into life world of society and person. Education in the spirit of piece, interconnection of moral and law education are important compounds of political education. One of the most important tasks of educational work should become world outlook culture forming of responsible pedagogue able to self-knowing, self- development, self- education. Pedagogical science and education which substantiates meaning of cultural and moral factors must act not as an object but as a subject of social order. Educational practices holding in pedagogical university must be based on moral senses of university idea.